Structuring of the economic potential components of seed enterprises (Economics and region, 2022)
From the correct identification of the economic potential components as an important economic category from the point of view of the systemic approach, the reliability of its assessment methodology and the development of further measures for its maximum return in the conditions of variability and uncertainty of the competitive environment, as well as increasing business performance, depend. Agricultural enterprises, in particular with seed specialization, have a powerful economic potential, the management of which is an important task of economic science. The article is devoted to the analysis of the researchers' theoretical views and the justification of the systematic approach to the structuring of the economic potential of seed enterprises. It was determined that the economic potential is a basic indicator of the economic growth of enterprises, industries and the national economy in general, and theoretical approaches to determining its components were analyzed. It has been proved that there is no unified approach to the definition and establishment of the components of economic potential in the scientific literature due to its multifaceted nature and the branch features of economic entities. The theoretical approach to the structuring of the economic potential is substantiated, with the identification of financial, labour, innovation, production, scientific and technological, environmental, information, marketing and management components, which are under the influence of various groups of innovations, characteristic of agrarian enterprises of the seed profile. The novelty of the obtained results lies in the deepening of the theoretical basis for the management of the economic potential of seed enterprises from the point of view of the innovations transfer and advanced achievements of Ukrainian agricultural genetics and selection into agricultural production. This will contribute to the maximum synergistic effect of the interaction and return of the components of the economic potential of enterprises, and, as a result, to the satisfaction of the interests of the stakeholders of the seed industry and the strengthening of food security in general.
Keywords: economic potential of the enterprise; seed enterprises; innovation transfer; resources; seed production; changing competitive environment; synergy